Promoting the process of determining brain death through standardized training - Su, Yingying; Zhang, Yan; Ye, Hong; Chen, Weibi; Fan, Linlin; Liu, Gang; Huang, Huijin; Gao, Daiquan; Zhang, Yunzhou (Frontiers in Neurology, 2024)
Objective: To explore the training mode for brain death determination to ensure the quality of subsequent brain death determination. Methods: A four-skill and four-step (FFT) training model was adopted, which included clinical neurological examination, electroencephalogram (EEG) examination, short-latency sensory evoked potential (SLSEP) examination, and transcranial Doppler (TCD) examination. Each skill is divided into four steps: multimedia theory teaching, bedside demonstration, one-on-one real or dummy simulation training and assessment. We analyzed the training results of 1577 professional and technical personnel who participated in FFT training mode from 2013 to 2020 (25 sessions), including error rate analysis of the written examination, knowledge gap analysis and influencing factors analysis. Results: The total error rates for the four written examination topics were all <5%, at 4.13% for SLSEP, 4.11% for EEG, 3.71% for TCD, and 3.65% for clinical evaluation. The knowledge gap analysis of the four skill test papers suggested that the trainees had different knowledge gaps. Based on univariate analysis and multiple linear regression analysis, among the six factors, specialty category, professional and technical title and hospital level were the independent influencing factors of answer errors (P < 0.01). Conclusion: FFT mode is suitable for BD determination training in China, but we should pay attention to the professional characteristics of participants, strengthen knowledge gap training and narrow the difference in training quality.